Psychometric properties of the Thai Qualifications Framework for Higher Education instrument among Royal Thai Air Force nurse stakeholders - Wannarit, La-Ongdao; Ritudom, Bangorn (Belitung Nursing Journal, 2024)
Background: The Thai Qualifications Framework for Higher Education (TQF: HEd) serves as a framework to enhance the quality of higher education in Thailand. However, no valid and reliable TQF: HEd instrument is available to measure the quality of graduates among Royal Thai Air Force Nurses. Objective: This study aimed to assess the psychometric properties of the TQF: HEd instrument among graduate nurses of the Royal Thai Air Force. Methods: Psychometric testing of the instrument was conducted. The instrument’s validity was evaluated through a review by a panel of five experts, providing a content validity index (CVI). Construct validity was assessed using Confirmatory Factor Analysis (CFA) with a sample size of 308, and Cronbach’s α coefficient was utilized to measure the scale’s internal consistency. Results: The Scale-Content Validity Index (S-CVI) was 0.88. CFA yielded the following fit indices: X2 = 265.861, p = 0.068, df = 233, X2/df ratio = 1.141, Comparative fit index (CFI) = 0.996, Tucker Lewis Index (TLI) = 0.993, Root Mean Square Error of Approximation (RMSEA) = 0.021, and Standardized Root Mean Square Residual (SRMR) = 0.033. The scale reliability was acceptable, with a Cronbach’s alpha coefficient of 0.93 and 0.85-0.92 for the six factors. Conclusion: The TQF: HEd instrument demonstrates satisfactory psychometric properties, which will be valuable for those in charge of the curriculum in utilizing the instrument to measure graduate competency and guide curriculum development.